Evaluate the integral of f(x, y, z) = x + z - 3 over the cylinder bounded by x^2 + y^2 = 1, z = 0 and z = 1.
the integral of f(x,y,z)=x+z-3 over the cylinder "x^2+y^2=1" ; z=0 and z=1 is;
"\\int^{1}_{0}\\int^{1}_{-1}\\int^{\\sqrt{1-y^2}} _{-\\sqrt{1-y^2}}(x+z-3)dxdydz"
"=\\int^{1}_{0}\\int^{1}_{-1}[(\\frac{x^2}{2}+xz-3x)]^{\\sqrt{1-y^2}}_{-\\sqrt{1-y^2}}dydz"
"=\\int^{1}_{0}\\int^{1}_{-1}2(z-3)\\sqrt{1-y^2} dydz"
"=\\int^{1}_{0}[2(z-3)\\int^{1}_{-1}\\sqrt{1-y^2}]dydz"
by letting "y=sin \\theta,\\implies dy=cos\\theta d\\theta" we then may evaluate the integral as
"=\\int^{1}_{0}[2(z-3)\\int^{1}_{-1}\\sqrt{1-y^2}dy]dz"
"=\\int^{1}_{0}[2(z-3)\\int^{\\pi\/2}_{-\\pi\/2}\\sqrt{1-sin ^2 \\theta} cos\\theta d\\theta ]dz"
"=\\int^{1}_{0}[2(z-3)\\int^{\\pi\/2}_{-\\pi\/2}cos ^2 \\theta d\\theta ]dz"
"=\\int^{1}_{0}[2(z-3). \\frac{1}{2}\\int^{\\pi\/2}_{-\\pi\/2}(1+cos2\\theta) d\\theta ]dz"
"=\\int^{1}_{0}(z-3)[\\theta+\\frac{1}{2}sin 2\\theta]^{\\pi\/2}_{-\\pi\/2}dz"
"=\\int^{1}_{0}(z-3)[(\\frac{\\pi}{2}+\\frac {1}{2}sin \\pi)- (-\\frac{\\pi}{2}+\\frac{1}{2}sin \\pi]dz"
"=\\pi\\int^{1}_{0}(z-3)dz"
"=\\pi[\\frac{z^2}{2}-3z]^{1}_{0}"
"=\\pi(\\frac{-5}{2})= \\frac{-5}{2}\\pi"
Comments
Leave a comment